2015
DOI: 10.1007/s00784-015-1686-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of therapeutic doses of radiotherapy on the organic and inorganic contents of the deciduous enamel: an in vitro study

Abstract: Preventive measures should be included in the patient treatment protocol because of RT-induced chemical changes to the deciduous enamel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
1
20
0
3
Order By: Relevance
“…In this regard, a previous follow-up study demonstrated that radiotherapy changed salivary properties and reduced the salivary flow and buffering capacity of individuals with Hodgkin's disease [Marangoni-Lopes et al, 2016]. Although the present study does not represent a real clinical condition of postradiation in the oral environment, we used a representative sample size and were able to demonstrate changes occurring in primary enamel and dentin, even at doses lower than those used previously [de Siqueira Mellara et al, 2014;de Sá Ferreira et al, 2016].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In this regard, a previous follow-up study demonstrated that radiotherapy changed salivary properties and reduced the salivary flow and buffering capacity of individuals with Hodgkin's disease [Marangoni-Lopes et al, 2016]. Although the present study does not represent a real clinical condition of postradiation in the oral environment, we used a representative sample size and were able to demonstrate changes occurring in primary enamel and dentin, even at doses lower than those used previously [de Siqueira Mellara et al, 2014;de Sá Ferreira et al, 2016].…”
Section: Discussionmentioning
confidence: 69%
“…When one considers that the lower the microhardness, the lower the mineral content, another important aspect to be investigated is the mineral composition of irradiated enamel and dentin. In this regard, an early study [de Sá Ferreira et al, 2016] evaluated the effects of radiotherapy on the composition of primary enamel and concluded that radiotherapy reduced the organic content of the primary enamel. However, in this study, the authors evaluated only the changes occurring in enamel after the final dose of 5,400 cGy.…”
Section: Introductionmentioning
confidence: 99%
“…), or even chemical changes such as reduction of calcium, phosphorus, carbonate and phosphate, and dentine crystallinity (De Sá Ferreira et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…In spite of its adhesion and polymerization mechanism, RelyX U200 resin cement had lower values of bond strength after radiotherapy, probably due to the reduction of calcium, phosphorus and carbon in the root dentine (De Sá Ferreira et al . ), which may generate fewer chemical bonds between cement and root dentine. In addition, the self‐adhesive materials require means of ionization for the chemical reaction, which altered by irradiation may reinforce this hypothesis (Mushashe et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation